Principles of layout and design the eye of the beholder - Winfield, Collette Mikesell; Christ, Jack; Insight Media (firm); Wisconsin Technical College System ([Waunakee, Wis.] : Wisconsin Technical College System Foundation, 1999)
The competent of this program is to use visual supports that increase readibility and clarity of documents, write a heading for a visual that will appear in a report or presentation, and designing visuals that match the movements of the eye
Executive producer, Laren Blumm, Sandra Carman ; producer, director, Dr. Jack Christ ; writer, Collette Mikesell Winfield
Featuring : Collete Mikesell Winfield, Dr. Jack Christ
Keywords: Graphic design (Typography); Design; Graphic arts; Visual aids